DESIGN OF A LIGHTNING STRIKE COUNTER TOOL IN THE MOJOSARI ULP DISTRIBUTION NETWORK BASED ON IOT - Maulana , Mochamad Rizal; Ahfas , Akhmad (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Electrical distribution systems frequently face disruptions, particularly in tropical climates like Indonesia, where lightning strikes are prevalent due to high humidity. Specific Background: These disruptions necessitate effective monitoring tools to manage lightning impacts on power distribution networks. Knowledge Gap: Despite existing solutions, there is a lack of real-time monitoring systems tailored for the specific conditions of Indonesian distribution networks. Aims: This study aims to develop an Internet of Things (IoT) based lightning monitoring device that leverages ACS712, DHT11, and LDR sensors, facilitating real-time data acquisition and notifications. Results: The system achieved sensor accuracies of 95.2% for the ACS712, 98.5% for the DHT11, and a satisfactory performance from the LDR sensor. The processed data is displayed on a 16x2 LCD and sent as notifications via Telegram. The device also includes a buzzer for immediate alerts during lightning strikes and features buttons for data logging and resets. Novelty: The research presents a novel application of IoT technology to create a user-friendly monitoring solution for lightning strikes, specifically designed for the 20KV distribution networks in the ULP Mojosari work area. Implications: By enabling timely notifications and efficient localization of lightning-related disruptions, this tool significantly enhances the operational response of field officers, improving the resilience of power distribution systems during adverse weather conditions. However, it is essential to note that the device requires an internet connection for Telegram notifications, and the ACS712 sensor has a maximum current reading limit of 30 amperes.